ISLAMIC CULTURAL NOTES IN ELT INSTRUCTION IN THE ISLAMIC BOARDING SCHOOLS OF HARAMAIN NAHDLATUL WATHAN NARMADA, WEST NUSA TENGGARA - Lalu Ari Irawan; Haerazi Haerazi (Akademika : Jurnal Pemikiran Islam, 2020)
Islamic contents and English were taught at Islamic Boarding School (IBS) Haramain Nahdlatul Wathan (NW) Narmada. English is taught as a general subject and compulsory subject as well. An English community (Language Asrama) is established by Kiai. It is aimed at practicing speaking English and exercising public speaking skills. IBS Haramain NW Narmada includes one of the IBSs in Indonesia in which it reflected Islamic values, cultures, and indoctrination in its teaching and learning. The pieces of evidence showed that this institution taught English for students (Santri) as a tool to gain global information around the world. Dealing with the ELT classrooms, IBS Haramian NW Narmada employed some learning strategies reflecting Islamic cultures and values such as syawir, Lalar, Hafal (memorizing), and Setoran (deposit). The strong emphasis on Arabic and English in daily communication addresses the immersion language program. It is a method applied to teach foreign languages. Based on the application, the IBS Haramain NW Narmada applied a total immersion program, in which Arabic and English are the target languages.